2004
DOI: 10.1158/0008-5472.can-03-2464
|View full text |Cite
|
Sign up to set email alerts
|

Radiation to Stromal Fibroblasts Increases Invasiveness of Pancreatic Cancer Cells through Tumor-Stromal Interactions

Abstract: Radiotherapy represents a major treatment option for patients with pancreatic cancer, but recent evidence suggests that radiation can promote invasion and metastasis of cancer cells. Interactions between cancer cells and surrounding stromal cells may play an important role in aggressive tumor progression. In the present study, we investigated the invasive phenotype of pancreatic cancer cells in response to coculture with irradiated fibroblasts. Using in vitro invasion assay, we demonstrated that coculture with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
296
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 339 publications
(306 citation statements)
references
References 41 publications
9
296
0
1
Order By: Relevance
“…Sublethal in vitro irradiation of rat 9L glioma cells resulted in the formation of a greater number of tumour satellites after injection of these irradiated cells into the striatum of rat brain. The ability of radiation to increase the expression of some MMPs and the invasiveness of cancer cells have also been reported for pancreatic cancer cells (Qian et al, 2002;Ohuchida et al, 2004), melanoma cells (Kaliski et al, 2005), rectal carcinoma cells (Speake et al, 2005), colon carcinoma cells and osteosarcoma cells (Wang et al, 2000).…”
Section: Discussionmentioning
confidence: 76%
“…Sublethal in vitro irradiation of rat 9L glioma cells resulted in the formation of a greater number of tumour satellites after injection of these irradiated cells into the striatum of rat brain. The ability of radiation to increase the expression of some MMPs and the invasiveness of cancer cells have also been reported for pancreatic cancer cells (Qian et al, 2002;Ohuchida et al, 2004), melanoma cells (Kaliski et al, 2005), rectal carcinoma cells (Speake et al, 2005), colon carcinoma cells and osteosarcoma cells (Wang et al, 2000).…”
Section: Discussionmentioning
confidence: 76%
“…Elevated expression and secretion of MK by the tumor might affect the surrounding stromal cells that express MK receptors in a paracrine mechanism and thereby contribute to the formation of the latter. Because it was shown that the stromal compartment in PDAC negatively affects radiation therapy (33,34) and creates a milieu for chemotherapy resistance (35,36), a fundamental issue in PDAC treatment, the role of MK in tumor stroma interplay and its effects on chemotherapy resistance requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were maintained as described previously. 25 We used quantitative real-time reverse transcription-PCR (qRT-PCR) to determine CLDN4 mRNA in formalin-fixed paraffin-embedded tissues of intraductal papillary mucinous neoplasms. In all, 80 formalin-fixed paraffin-embedded tissue samples of intraductal papillary mucinous neoplasms and 8 formalin-fixed paraffin-embedded tissue samples of pancreatic ductal adenocarcinomas obtained from patients undergoing pancreatic resection at our department (Kyushu University Hospital, Fukuoka, Japan) from 1987 to 2008 were selected for the present study based on the availability of sufficient quantities of neoplastic cells.…”
Section: Cultured Cells and Pancreatic Tissues As The Clinical Samplementioning
confidence: 99%